Ozone reactor technology - Padmanabhan, K. (Anshan Ltd, 2014)
This is a comprehensive guide to the technology of ozone, its production and applications in various fields. It has been written by a team of academic experts who have actually involved themselves in promoting the use of ozone. There are in total fourteen chapters giving a complete guide to the technological information required concerning ozone gas, how it can be generated, how to design ozone reactors and how to apply it for various applications. Very important is the development of circuits for generating ozone as well as the in situ ozone system newly developed by the editor's own group of colleagues after a fifteen year research period. Applications of ozone in water and waste water treatment are covered, and also the use of ozone for tannery effluent treatment and textile applications. There is also useful technical information for effluent treatment areas, a chapter on ozone for mosquito control, another on its use for medical applications, and finally food and biological treatment applications are also covered. This book will be an excellent reference work for both academic chemists and professionals working in industry and commercial organizations.